2021
DOI: 10.1016/j.nicl.2021.102807
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine transporter binding in symptomatic controls and healthy volunteers: Considerations for neuroimaging trials

Abstract: Highlights Symptomatic controls have higher putaminal DAT binding than healthy controls. The difference could be due to selection/self-selection bias or upregulation. The effect should be taken into account when neuroimaging trials are designed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
2
2
Order By: Relevance
“…Therefore, our study confirms that striatal monoamine availability in DIP is normal. However, our result differs from that of a recent study of dopamine transporters in symptomatic controls and healthy subjects that found symptomatic controls with essential tremor, vascular parkinsonism, or DIP to show higher putaminal dopamine transporter binding than healthy subjects 7 . Heterogeneity of symptomatic controls and selection bias in enrolling healthy subjects might explain that conflicting result.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, our study confirms that striatal monoamine availability in DIP is normal. However, our result differs from that of a recent study of dopamine transporters in symptomatic controls and healthy subjects that found symptomatic controls with essential tremor, vascular parkinsonism, or DIP to show higher putaminal dopamine transporter binding than healthy subjects 7 . Heterogeneity of symptomatic controls and selection bias in enrolling healthy subjects might explain that conflicting result.…”
Section: Discussioncontrasting
confidence: 99%
“…The mean putamen and posterior-putamen SBR values were similar to those previously published [ 12 ]. These results are not consistent with those of a recent study [ 14 ] showing that the mean SBR values of Hv ( n = 48) and of patients without dopaminergic degeneration ( n = 70) were similar for all VOIs except for the posterior putamen VOI for which values were 8% higher for the patients. As suggested by the authors, this difference could be explained by a selection bias, thereby highlighting the importance of a large sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…No significant difference was observed between databases from Hv and those from patients without dopaminergic neurodegenerative pathology. However, these results are still debated, as SBR could also depend on comorbidities; recent study found that the mean posterior putamen SBR value was 8% higher in a group of symptomatic patients without dopaminergic neurodegenerative pathology than in a group of Hv [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of molecular imaging, DAT uptake levels have become a reliable indicator for evaluating PD progression [ 15 ]. This is a more objective approach than the UPDRS score and is rarely used to assess the effects of antihypertensive drugs on PD [ 7 , 16 ].…”
Section: Introductionmentioning
confidence: 99%